2004
DOI: 10.1097/01.alc.0000107200.88229.57
|View full text |Cite
|
Sign up to set email alerts
|

Effective Strategies for Recruiting Families Ascertained Through Alcoholic Probands

Abstract: Results provide insight into successful strategies for recruiting large numbers of participants and their family members selected for a condition associated with a social stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
0
22
0
3
Order By: Relevance
“…Computer use may not be equal across demographic groups, possibly creating biased samples (Etter & Perneger, 2001;Scholle et al, 2000). Finally, Internet recruitment may not be an effective tool for studies recruiting locally, since it may be harder to target a specific geographic area (Seaton, Cornell, Wilhelmsen, & Vieten, 2004). The Internet may be more successful when used in conjunction with traditional recruitment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Computer use may not be equal across demographic groups, possibly creating biased samples (Etter & Perneger, 2001;Scholle et al, 2000). Finally, Internet recruitment may not be an effective tool for studies recruiting locally, since it may be harder to target a specific geographic area (Seaton, Cornell, Wilhelmsen, & Vieten, 2004). The Internet may be more successful when used in conjunction with traditional recruitment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Purchase of such demographically defined mailing or telephone lists has become a more frequent strategy for recruiting participants across a wide range of research domains, including infant development (Kraebel & Gerhardstein 2006), alcoholism (Seaton et al, 2004), adolescent gambling (Winters et al, 1993), cancer prevention (Bowen et al, 2004), and health promotion (Hays et al, 2003). Information provided by the company indicated that the phone numbers were compiled from the following sources: Lamaze classes, baby registries, mail order purchases, magazine subscriptions, and questionnaire data.…”
Section: Recruitment Strategies and Costsmentioning
confidence: 99%
“…No inclusion/exclusion criteria were applied aside from the ability to respond to the telephone interview and complete the questionnaires. The details of recruitment of all participants have been previously published [see Seaton et al, 2004; Veiten et al, 2004]. …”
Section: Methodsmentioning
confidence: 99%
“…Test-retest and inter-rater reliability for clinical data have been shown to be very good [Vieten et al, 2004]. Design, methods, recruitment strategies and sample demographics of the UCSF Family Alcoholism Study have been presented previously [see Seaton et al, 2004; Vieten et al, 2004], along with intrafamilial correlations for primary diagnostic phenotypes.…”
Section: Introductionmentioning
confidence: 99%